2016
DOI: 10.13075/ijomeh.1896.00798
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early return to work after a coronary artery bypass graft surgery (CABG)

Abstract: International Journal of Occupational Medicine and Environmental CABG). Material and Methods:Two hundred twenty-six working patients who volunteered and underwent a primary coronary artery bypass surgery between September 2013 and May 2014 were selected for the study and followed up for 6 months. Predictors of early return to work (RTW) (within 2 months) were analyzed from variables in a prospectively collected database and the 36-Item Short Form Health Survey (SF-36) questionnaire carried out in the hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
0
22
2
Order By: Relevance
“…25,26 Psychosocial factors have long been understood to influence outcomes after intervention in cardiac, orthopaedic, gynecologic, urologic, gastrointestinal, and transplant surgeries. 18,31,35,42,43 Specifically, these factors include mood, attitude toward surgery, social support, coping, and personality. The association between mental health and RTW has not been previously demonstrated among patients undergoing rotator cuff repair, but our findings mirror previous literature regarding psychological influences on return to sport in anterior cruciate ligament reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Psychosocial factors have long been understood to influence outcomes after intervention in cardiac, orthopaedic, gynecologic, urologic, gastrointestinal, and transplant surgeries. 18,31,35,42,43 Specifically, these factors include mood, attitude toward surgery, social support, coping, and personality. The association between mental health and RTW has not been previously demonstrated among patients undergoing rotator cuff repair, but our findings mirror previous literature regarding psychological influences on return to sport in anterior cruciate ligament reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings go along with an Iranian study of 248 patients after coronary bypass surgery, where the probability of returning early to work was 2.3 times higher in patients with job stress. [46] We assume that patients who report a higher perception of work stress may hold a leading position with a higher degree of personal identification and recognition, resulting in a greater motivation to return to work. This interpretation is quite speculative, but may be supported by the fact that the proportion of patients who returned to work was significantly higher by 14 percentage points in highly educated versus less-educated patients (78% vs. 64%).…”
Section: Plos Onementioning
confidence: 99%
“…In contrast to a study that didn't find a significant association between pre-HRQOL and post-surgery level in patients after cardiac surgery [8]. [16]. This study conducted to identify factors determines early return to work after six months of CABG.…”
Section: Hrqol After Cardiac Surgery and Related Factorsmentioning
confidence: 86%
“…The study identified four new medical factors that could be used as predictors of early return to work after CABG. These factors are: normal serum troponin T level, shorter pump time in surgery, normal mean arterial pressure (MAP) before the surgery and higher serum magnesium (Mg) levels [16].…”
Section: Hrqol After Cardiac Surgery and Related Factorsmentioning
confidence: 99%